Plurality of “Spuntos” and Audio-Tactile Format: aLook at Collective Musical Improvisation (Itinera, 2015)
This paper looks at the interactional-improvisational aesthetic experience based on Luigi Pareyson’s notions of “formativity” and “spunto” as well as on the concepts and the taxonomy of Vincenzo Caporaletti’s audiotactile formativity theory. On the theoretical ground, we propose a deeper investigation of the key concepts in the audio tactil phenomenology, such as the “audiotactile principle” [ATP] and the “audiotactile conceptual schemes”. Original concepts for the study of musical interaction are also developed, noticeably the notion of the “interactional formative space” [IFS].